The Effect of using the Mobile Application of JKN Health Social Security Implementing Agency on JKN-KIS Participant Satisfaction in the City of Padang using the Unified Theory of Acceptance and use of Technology Model - Debi Mersah Putra; Alfitman; Verinita (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of the use of the JKN mobile application by the health social security administering agency on the satisfaction of JKN-KIS participants in the city of Padang using the unified theory of acceptance and use of technology model. This research is causality research, the method used is quantitative. The population that will be used is all JKN KIS participants in the city of Padang who have used the Mobile JKN application in April 2022 with a total of 101,676 people, the sample is 470 JKN KIS participants in the city of Padang who have used the Mobile JKN application. The sampling technique used in the form of non-probability sampling method with purposive sampling technique. The sample criteria are as follows: have become JKN participants, JKN participants in Padang City, already registered and using the JKN mobile application. Analysis of this research data using Structural Equation Modeling - Partial Least Square (SEM-PLS). The conclusions in this study are as follows: performance expectancy has a significant influence on the use behavior of mobile JKN, eﬀort expectancy does not have a significant influence on use behavior of mobile JKN, social influence has a significant influence on use behavior of mobile JKN, facilitating conditions do not have a significant influence on use behavior mobile JKN, hedonic motivation has a significant influence on the use behavior of mobile JKN, perceived value has no significant effect on use behavior of mobile JKN, habit has no significant effect on use behavior of mobile JKN, use behavior of mobile JKN has a significant influence on user satisfaction.